(untitled) - Birdsall, Stephen S (New York, 1990)
This book is about the geography of the United States. and although we look at the country's physical geography, our central interest is not landforms, climate, soils, or vegetation but the human imprint on the landscape.
Keywords: America,America; Description and travel,History